Morphology of immature stages and mating behavior in Liogenys fusca (Blanchard) (Coleoptera, Melolonthidae, Melolonthinae) - Rodrigues,Sérgio Roberto (2016)
ABSTRACT Liogenys fusca is a rizophagous insect pest in various crops of economic importance in Brazil. Here we investigated the morphology of immature stages and mating behavior of this species. The redescription of the 3rd instar larvae of L. fusca in this work allows identification and registration of occurrence independently of adults, which occur sporadically in a certain period of the year. Male and female of L. fusca remained confined in the soil during the day and exited between 19:00 and 23:30 h. The copulations occurred between 19:30 and 21:00 h, and were characterized by a typical behavioral sequence. Copulation durations in L. fusca lasted on average 512.23 s. Adults were observed feeding before the copulations on leaves and inflorescences of plant species belonging to the family Anacardiaceae, Myracrodruon urundeuva, Schinus terebinthifolius, Astronium fraxinifolium and Anacardium occidentale.